2023
DOI: 10.17135/jdhs.2023.23.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Types of Ramen Sauce on Bovine Tooth Discoloration

Abstract: Background: This study aimed to determine the effect of ramen sauce on tooth tone changes over time, after selecting three different ramen colors from the ramens sold in the market, and applying the sauce to bovine teeth. Methods: Healthy bovine teeth were selected, and cutting discs were used to produce 60 specimens (5×5×3 mm), with 15 specimens distributed per county. Three types of ramen (buldak, chacharoni black bean sauce, and ottogi curry noodle) were used as the experimental group, and water was used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Previous studies on color changes of teeth associated with food have reported that foods such as red pepper paste, coffee, tea, and instant noodles can cause tooth discoloration [17][18][19][20] . According to a study by Kim et al 18) , tannin compounds found in coffee and black tea can reduce bacterial plaque in the oral cavity; however, tannins' black pigments can bind to protein components, leading to tooth discoloration and reduced lightness.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on color changes of teeth associated with food have reported that foods such as red pepper paste, coffee, tea, and instant noodles can cause tooth discoloration [17][18][19][20] . According to a study by Kim et al 18) , tannin compounds found in coffee and black tea can reduce bacterial plaque in the oral cavity; however, tannins' black pigments can bind to protein components, leading to tooth discoloration and reduced lightness.…”
Section: Discussionmentioning
confidence: 99%